Bayesian forecast of the basic reproduction number during the Covid-19 epidemic in Morocco and Italy. Issue 4 (2nd October 2021) - El Fatini, Mohamed; El Khalifi, Mohamed; Gerlach, Richard; Pettersson, Roger
ABSTRACT: In a Covid-19 susceptible-infected-recovered-dead model with time-varying rates of transmission, recovery, and death, the parameters are constant in small time intervals. A posteriori parameters result from the Euler-Maruyama approximation for stochastic differential equations and from Bayes' theorem. Parameter estimates and 10-day predictions are performed based on Moroccan and Italian Covid-19 data. Mean absolute errors and mean square errors indicate that predictions are of good quality.